Pro SQL Server Disaster Recovery - Luetkehoelter, James (Springer, 2017)
Many would argue that the single most important job of a SQL Server database administrator is to be able to recover your database in the event of loss or damage. Pro SQL Server Disaster Recovery helps you meet that goal by showing you how to think about and plan for potential problems. You'll learn to anticipate and reduce the likelihood of a disaster, and to mitigate the effects of a disaster when one does occur. Perhaps most importantly, you'll learn how to prepare so that you can return a system to its normal state quickly, ensuring system availability and the continued success and operation of your business.